1972
DOI: 10.1037/h0033027
|View full text |Cite
|
Sign up to set email alerts
|

Communication of interpersonal evaluations.

Abstract: Condition Low acquaintance, Origin -self Receiver -friend Receiver -evaluatee Low acquaintance, Origin -other Receiver -friend Receiver -evaluatee High acquaintance, Origin -self Receiver -friend Receiver -evaluatee High acquaintance, Origin -other Receiver -friend Receiver -evaluatee

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
81
0
3

Year Published

1987
1987
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(88 citation statements)
references
References 18 publications
3
81
0
3
Order By: Relevance
“…It is also the case that perceivers are less willing to express negative expectancies directly, or even indirectly, because of good manners, charity, or fear of the consequences (Blumberg, 1972;Shrauger, 1982). This pattern has been demonstrated in several studies in which perceivers given a negative (e.g.. cold, unsociable, dull) expectancy about a target behaved even more positively to targets than those given a positive expectancy (Bond, 1972;Ickes, Patterson, Rajecki, & Tanford, 1982;Major et aL, 1986;Swann & Snyder, 1980).…”
Section: Characteristics Of the Expectancymentioning
confidence: 99%
See 1 more Smart Citation
“…It is also the case that perceivers are less willing to express negative expectancies directly, or even indirectly, because of good manners, charity, or fear of the consequences (Blumberg, 1972;Shrauger, 1982). This pattern has been demonstrated in several studies in which perceivers given a negative (e.g.. cold, unsociable, dull) expectancy about a target behaved even more positively to targets than those given a positive expectancy (Bond, 1972;Ickes, Patterson, Rajecki, & Tanford, 1982;Major et aL, 1986;Swann & Snyder, 1980).…”
Section: Characteristics Of the Expectancymentioning
confidence: 99%
“…Because most people have generally favorable self-conceptions (Swann, Griffin, & Ely, 1982), it is consistent with their self-identity to confirm a positive expectancy. Furthermore, because most people prefer positive over negative feedback and prefer to have others view them in a positive light (McFarlin & Blascovich, 1981;Shrauger, 1975), confirming a positive expectancy also is consistent with self-presentational concerns.It is also the case that perceivers are less willing to express negative expectancies directly, or even indirectly, because of good manners, charity, or fear of the consequences (Blumberg, 1972;Shrauger, 1982). This pattern has been demonstrated in several studies in which perceivers given a negative (e.g.. cold, unsociable, dull) expectancy about a target behaved even more positively to targets than those given a positive expectancy (Bond, 1972;Ickes, Patterson, Rajecki, & Tanford, 1982;Major et aL, 1986;Swann & Snyder, 1980).…”
mentioning
confidence: 99%
“…Indeed, relationally close individuals avoid evaluating each other (Goffman, 1959). When they have no choice but to communicate information about each other, close individuals either distort the communication to make it more consistent with their partner's self-concept (Manis, Cornell, & Moore, 1974) or discuss each other's positive rather than negative traits (Blumberg, 1972). As Tesser and Rosen (1975) put it, among close individuals, good news tends to be communicated more frequently, more quickly, more fully, and more spontaneously than bad news" (the MUM effect; p. other with support, which regulates or alleviates negative affect (e.g., depression and stress; Cohen & Wills, 1985;Coyne, Burchill, & Stiles, 1991;Sarason, Sarason, & Pierce, 1990) and increases positive affect, feelings of well-being, and self-esteem (Cohen & Hoberman, 1983;Major, Testa, & Bylsma, 1991).…”
Section: The Relationships -As-enabler Hypothesismentioning
confidence: 99%
“…These sources would compensate for the lack of other confirmatory indicators, such as status, expertise, interpersonal connections, direct access to information, and so forth, that are generally more available in face-to-face conversations with known players. Ayim (1994) also portrayed gossipers as intent on establishing the veracity of gossip, although Blumberg (1972) remarked that extensive monitoring of gossip over time is unlikely and impractical. In either case, the inclination to gossip covertly, anonymously, or vicariously betrays an awareness of the violation of privacy norms.…”
mentioning
confidence: 99%
“…(In the case of positive gossip about a person, the gossiper is spared being obsequious while buoying the target's reputation with a "third-party endorsement.") Blumberg (1972), finding strong evidence that evaluations traveling through the network tend to stop short of their targets, concluded that a norm seems to exist "to keep people from learning too much about what others think of them" (p. 161). Wert and Salovey (2004), in this issue, also acknowledge that gossip affords one the benefits of various veins of social comparison while avoiding the risks of embarrassment or confrontation.…”
mentioning
confidence: 99%